Linguistic etiquette: a review from a pragmatic perspective - Loae Fakhri Jdetawy,; Mohd Hilmi Hamzah, (Technium Social Sciences Journal, 2020)
This current article reviews the notion of ‘linguistic etiquette’ from a pragmatic perspective. Linguistic etiquette refers to the system of norms and rules of polite speech behaviour which maintains an observance that ensures the existence of polite communication and the appropriateness of the linguistic action in any communicative event. Particularly, this article aims to explore the nature of linguistic etiquette and identify its rules, principles, and strategies. The findings of this article demonstrated that all speakers of any linguistic background are always in need to develop a set of verbal and non-verbal etiquette behaviour rules, adopt them in certain social circles and conditions, adhere to them in any practice of communication, and avoid violating them. Besides, certain norms of verbal behaviours are established and enshrined specifically for a particular society and these norms are instilled in the members of this society during their early childhood. Such norms represent the basic formulas of linguistic etiquette that are implemented at different language levels. As a pragmatic and a sociolinguistic routine, linguistic etiquette falls under the concept of politeness. The elements of linguistic etiquette are present in every conversation. Further, linguistic etiquette consists of the principles of brevity, relevance, literacy, accuracy, and the correct attitude towards the interlocutor. Finally, the findings of the current article concluded that in order to master linguistic etiquette, the interlocutors should observe and pay attention to the features of ‘speech culture’ which include the correctness of speech, the logicality of speech, the purity of speech, the accuracy of speech, linguistic ‘weeds’, speech expressiveness, speech tone, and the rules of speech behaviour.